Dolny Śląsk i Saksonia jako wspólny obszar gospodarczy - aspekty marketingowe i przestrzenne - Adamczuk, Franciszek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
This article discusses interregional co-operation between Lower Silesia and Saxony. In particular it presents the conception of creating common economic area in this part of Europe. The author presents spatial, economic and marketing aspects in the context of preparing. The Lower Silesia Development Strategy to the 2020 year and others - earlier prepared documents. The last part of the article contains conclusions and assessment of the analyzed problem's, which can be used to improve the co-operation between these regions. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1147, s. 11-18